Thermal Hydraulics Analysis of the Distribution Zone in Small Modular Dual Fluid Reactor - Chunyu Liu; Xiaodong Li; Run Luo; Rafael Macian-Juan (Metals, 2020)
The Small Modular Dual Fluid Reactor (SMDFR) is a novel molten salt reactor based on the dual fluid reactor concept, which employs molten salt as fuel and liquid lead/lead-bismuth eutectic (LBE) as coolant. A unique design of this reactor is the distribution zone, which locates under the core and joins the core region with the inlet pipes of molten salt and coolant. Since the distribution zone has a major influence on the heat removal capacity in the core region, the thermal hydraulics characteristics of the distribution zone have to be investigated. This paper focuses on the thermal hydraulics analysis of the distribution zone, which is conducted by the numerical simulation using COMSOL Multiphysics with the CFD (Computational Fluid Dynamics) module and the Heat Transfer module. The energy loss and heat exchange in the distribution zone are also quantitatively analyzed. The velocity and temperature distributions of both molten salt and coolant at the outlet of the distribution zone, as inlet of the core region, are produced. It can be observed that the outlet velocity profiles are proportional in magnitude to the inlet velocity ones with a similar shape. In addition, the results show that the heat transfer in the center region is enhanced due to the velocity distribution, which could compensate the power peak and flatten the temperature distribution for a higher power density.